2015
DOI: 10.11118/actaun201563041417
|View full text |Cite
|
Sign up to set email alerts
|

Soil Scientific Research Methods Used in Archaeology - Promising Soil Biochemistry: a Mini-review

Abstract: VRANOVÁ VALERIE, DANSO MARFO THEODORE, REJŠEK KLEMENT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…In below-ground conditions it is harder to preserve intact starch grains. In a field experiment that compared the survival rate of starch grains on grinding stones placed on the ground surface and below ground, it was shown that the samples taken from the experimental grinding stones on the soil surface contained better preserved starch grains (Barton, 2009;Vranová et al, 2015). Despite such observations, starch granules are well preserved at many archaeological sites (Fullagar et al, 1998;Therin et al, 1997).…”
Section: Sampling Of Starch From Soil Samplesmentioning
confidence: 99%
“…In below-ground conditions it is harder to preserve intact starch grains. In a field experiment that compared the survival rate of starch grains on grinding stones placed on the ground surface and below ground, it was shown that the samples taken from the experimental grinding stones on the soil surface contained better preserved starch grains (Barton, 2009;Vranová et al, 2015). Despite such observations, starch granules are well preserved at many archaeological sites (Fullagar et al, 1998;Therin et al, 1997).…”
Section: Sampling Of Starch From Soil Samplesmentioning
confidence: 99%
“…However, the ratio of humic to fulvic acids as well as its change due to the agrogenic transformation of the soil has been little studied, especially in the archaeological sites. According to Vranova et al (2015), the studies of various organic compounds, such as lipids and proteins, are most emphasized. Meanwhile, the ratio of humic to fulvic acids shows the link between humification and mineralization, as well as the intensity and sustainability of soil use in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus was detected in selected samples in specific clusters and mainly in the top layers L1to L4 with one occurrence in L6. Its presence in the top layers testifies use of the area either for disposal of waste with high organic matter content, animal remains or even food residue (Vranova, Marfo Th, and Rejsek 2015).…”
Section: Methodology and Analysismentioning
confidence: 99%